Quality of life of elderly caring for an elderly family member: systematic review (Research, Society and Development, 2023)
One of the consequences of the aging process is the increased prevalence of chronic degenerative diseases, causing the elderly to lose their autonomy and independence, requiring help in their daily tasks. Objective: to analyze the scientific production that addresses the quality of life (QoL) of family caregivers (60 years or older) who take care of another elderly person in a family environment, based on primary articles. The specific objectives were: to identify QoL, aspects of care, and intervention with elderly family caregivers. Method: registered with PROSPERO. The articles were identified by the bases: PubMed, Embase, WOS, Scopus, Cinhal, and Lilacs – from 1988 to 2021, according to the eligibility criteria. Results: Of 1,143 selected articles, ten were included, according to the PRISMA instructions. The concept of quality of life adopted had multidimensional perspectives. Subjective aspects stood out as essential for the assessment and understanding of QoL. Different instruments were used and one of them developed a specific scale for caregivers of elderly people with dementia (DQoL-OC). Most caregivers were women and assisted elderly people with different health problems, emphasizing dementia. Conclusion: analyzing the QoL of elderly family caregivers is extremely relevant, as well as the intervention process adapted to the health and well-being of this individual, which proved to be potential means of improving the QoL of elderly family caregivers. Therefore, the deepening of this theme is relevant in view of the growing number of elderly people worldwide.